Violation of the Maxim of Politeness in the Novel Teruslah Bodoh Jangan Pintar by Tere Liye - Maghfiroh, Hayatin Nur; Wini Tarmini (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
Indonesian society is known as a society that has a friendly attitude and a strong culture of politeness. However, in practice in everyday life, quite a few speakers violate language politeness maxims. Violations of language politeness maxims can also be found in the novel. In this era, quite a few people choose novels as a means of entertainment, especially for generation Z. It is very worrying if violations of language politeness maxims become acceptable and become a language reference for today's generation. The aim of this research is to describe forms of violation of language politeness maxims in novels “Teruslah Bodoh Jangan Pintar” by tere Liye. The method used is a qualitative research approach. Data collection techniques use listening and note-taking techniques. The research results showed that there were 78 utterances that contained violations of the politeness maxims of Leech's theory as follows: 28% violation of the tact maxim; 12% the generosity maxim; 32% violation of the praise maxim; 13% violation of the modesty maxim; 14% violation of agreement maxim, and 1% violation of the sympathy maxim. The implication of this research is that the characters' speech can serve as an illustration for readers regarding violations of language politeness maxims in accordance with Leech's theory.